"Road to Rio": A case study of workload periodization strategy in Rugby-7s during an Olympic season - Robineau, J.; Marrier, B.; Le Meur, Y.; Piscione, J.; Peeters, A.; Lacome, M. (Frontiers in Sports and Active Living, 2019)
The objective of this manuscript was to examine the periodization strategy of an international Rugby-7s team during an Olympic season. Training load data were collected in fourteen elite male players over a 48-week period during the 2015-2016 Olympic season. The season consisted of 3 macrocycles including: preseason (12-wk duration), in-season (25-wk) fragmented into four 4-7 week mesocycles (In-1 to 4) and the final preparation for the Rio 2016 Olympic Games (Olympic preparation, 11-wk). External training load (TL) such as the total distance (TD), the high-intensity distance (HID) and the number of accelerations performed, was monitored in training and competition over the entire duration of the season using a global positioning system (GPS) devices. The rating of perceived exertion (RPE) was multiplied by the session duration (min) to provide an internal TL (session-RPE) value for all training sessions and competitions. The Olympic preparation may enable planning of higher external TL compared to the preseason (TD, 21±13%, moderate; total accelerations, 27±4%, moderate) whereas no difference was observed for internal TL values between these two periods. High-intensity distance (HID) and internal TL (session-RPE) were lower (-11.0±7.8%, small and -38±3%, moderate, respectively) during the in-season compared to preseason. Internal TL, TD as well as HID were lower in the third in-season mesocycle (In-3) compared with the first in-season mesocycle (In-1) (-25±12%, moderate; -32±4%, moderate; -49±8%, moderate, respectively). The staff managed the workload considering the in-season as the main part of the "Road to Rio". The strategy to reduce the workload at the middle of the season and to induce weeks of regeneration at the end of the in-season was highlighted by the training availability of 100% of the squad at the beginning of the Olympic preparation. The workload periodization strategy of an Olympic season differs from the strategy previously described during a non-Olympic season.